2018
DOI: 10.1039/c7rp00177k
|View full text |Cite
|
Sign up to set email alerts
|

‘What do you think the aims of doing a practical chemistry course are?’ A comparison of the views of students and teaching staff across three universities

Abstract: The aims of teaching laboratories is an important and ever-evolving topic of discussion amongst teaching staff at teaching institutions. It is often assumed that both teaching staff and students are implicitly aware of these aims, although this is rarely tested or measured. This assumption can lead to mismatched beliefs between students and teaching staff and, if not corrected for, could lead to negative learning gains for students and become a source of frustration for teaching staff. In order to measure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…In the Framework for Learning in the Chemistry laboratory proposed by Seery (ASAP), one of the four principles stated that laboratory courses should have some focus on practical techniques. Most instructors' expect students to learn lowerorder skills such as practical techniques in a laboratory course (Bruck, et al, 2010;Bruck and Towns, 2013;George-Williams, et al, 2018). Here we have shown students already possess the knowledge of how to perform certain techniques.…”
Section: Implications For University Laboratory Coursesmentioning
confidence: 63%
See 1 more Smart Citation
“…In the Framework for Learning in the Chemistry laboratory proposed by Seery (ASAP), one of the four principles stated that laboratory courses should have some focus on practical techniques. Most instructors' expect students to learn lowerorder skills such as practical techniques in a laboratory course (Bruck, et al, 2010;Bruck and Towns, 2013;George-Williams, et al, 2018). Here we have shown students already possess the knowledge of how to perform certain techniques.…”
Section: Implications For University Laboratory Coursesmentioning
confidence: 63%
“…Vygotsky proposed that the amount of new knowledge a student can learn is inextricably linked to what they know already, which is termed the zone of proximal development (ZPD) (Vygotsky and Cole, 1978). In field of laboratory education there has been a great deal of discussion concerning the skills that students should learn through laboratory education (Kirschner and Meester, 1988;Hofstein and Lunetta, 2004;Reid and Shah, 2007;Bruck, et al, 2010;Bruck and Towns, 2013;George-Williams, et al, 2018). Recently, a framework for learning in the laboratory has been proposed, based upon the prior literature (Seery, et al).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the purpose of laboratory learning, students' opinions included; the development of practical and scientific process skills, as well as enhancing understanding of the theoretical concepts (Dikmenli, 2009;George-Williams et al, 2018;Hanif et al, 2009), learning science by fun (Aykutlu et al, 2019;Harman et al, 2016;Sadoglu & Durukan, 2018), effective and meaningful learning (Dikmenli, 2009;Harman et al, 2016), motivation and the development of positive attitude towards science (Dikmenli, 2009), permanent learning and the application of learned concepts (Harman et al, 2016), verification of known scientific theories and principles, conceptual understanding of the nature of science, creation of a link between scientific knowledge and contemporary experiences, and the creation of a link between science, technology, and society (Dikmenli, 2009). With the use of metaphors, students described the purpose of the science laboratory as learning for curiosity, learning by direction and learning by labour (Aykutlu et al, 2019).…”
Section: Aims and Purposes Of Laboratory Learningmentioning
confidence: 99%
“…With the use of metaphors, students described the purpose of the science laboratory as learning for curiosity, learning by direction and learning by labour (Aykutlu et al, 2019). George-Williams et al's (2018) study stated the purpose as imparting the knowledge of scientific ways of reasoning and the appropriate use of scientific language. Also, students indicated that laboratory instruction is meant to assist them in learning about their learning abilities and developing everyday scientific problem-solving and critical thinking skills (Yildirim, 2016).…”
Section: Aims and Purposes Of Laboratory Learningmentioning
confidence: 99%
See 1 more Smart Citation